1996
DOI: 10.1590/s0074-02761996000200020
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, immunological and toxicological characteristics of the crystal proteins of Bacillus thuringiensis subsp. medellin

Abstract: Characterization of the insecticidal and hemolytic activity of solubilized crystal proteins of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The size of the parasporal inclusion produced by the recombinant strain Bti 4Q2-81 (pBTM3) were bigger than those produced by the wild type strains of Btmed and Bti, contrasting the results of Delécluse et al (1993) who observed that the Bti 4Q2-81 recombinant strain harboring the cry4B gene produced smaller inclusions, while the Bti 4Q2-81 recombinant strain harboring the (Orduz et al 1996), contrary to the observation of Chilcott and Ellar (1988) on Bti, where they found that in this Bt subspecies the most toxic component of the crystal was the 68 kDa protein. It has been suggested that proteins of 68 and 30 kDa of Btmed have a minor role in toxicity towards C. quinquefasciatus larvae (Orduz et al 1996). Toxicity of the recombinant Cry4A protein of Bti is between 21-and 22-times lower than the recombinant 94 kDa protein of Btmed in Aedes and Culex species as indicated by the toxicity data reported by Angsuthanasombat et al (1992), although there were differences in the larval age in the two bioassays being compared.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The size of the parasporal inclusion produced by the recombinant strain Bti 4Q2-81 (pBTM3) were bigger than those produced by the wild type strains of Btmed and Bti, contrasting the results of Delécluse et al (1993) who observed that the Bti 4Q2-81 recombinant strain harboring the cry4B gene produced smaller inclusions, while the Bti 4Q2-81 recombinant strain harboring the (Orduz et al 1996), contrary to the observation of Chilcott and Ellar (1988) on Bti, where they found that in this Bt subspecies the most toxic component of the crystal was the 68 kDa protein. It has been suggested that proteins of 68 and 30 kDa of Btmed have a minor role in toxicity towards C. quinquefasciatus larvae (Orduz et al 1996). Toxicity of the recombinant Cry4A protein of Bti is between 21-and 22-times lower than the recombinant 94 kDa protein of Btmed in Aedes and Culex species as indicated by the toxicity data reported by Angsuthanasombat et al (1992), although there were differences in the larval age in the two bioassays being compared.…”
Section: Discussionmentioning
confidence: 69%
“…Recombinant Lambda Zap DNA was packed in vitro and used to infect an E. coli XL1-BLUE host. Library was plated and plaques were transferred to nitrocellulose membranes to be probed with a mouse antiserum raised against the 94 kDa crystal protein of Btmed (Orduz et al 1996). After purification of the positive plaques, one of them was selected for further characterization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cry type of proteins are toxic to different orders of insect such as Lepidoptera, Diptera and Coleoptera. The Cyt proteins with molecular weight between 25 and 30 kDa display cytolytic and mosquitocidal activity (Chilcott & Ellar 1988, Koni & Ellar 1994, Orduz et al 1996; however, the mosquitocidal activity is lower than the Cry toxins (Chang et al 1993, Crickmore et al 1995, Orduz et al 1996.…”
mentioning
confidence: 99%